Existence of normal complement to the Hall subgroup - Romanovsky , A. V.; Sementovsky , A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A sufficient condition is obtained for the existence of a normal complement of a Hall subgroup, depending on the degrees of a specific set of irreducible characters of the group.